A Quantitative Analysis of the Spontaneous Reporting of Congestive Heart Failure‐Related Adverse Events With Systemic Anti‐Fungal Drugs. (16th May 2013) - Hauben, Manfred; Hung, Eric Y.
Abstract To investigate spontaneous reporting relationships between representative antifungal agents and congestive heart failure (CHF)‐related adverse events (AE) we performed multiple disproportionality analyses of the US FDA AERS database. Specifically we performed analysis of drug‐AE associations (2D) plus drug–drug–AE and drug–AE–AE‐associations (3D), the latter two to explore the potential contribution of reported pharmacodynamic interactions, overexposure from pharmacokinetic interactions, and drug overdose. Itraconazole displayed a pattern of statistical reporting dependencies across multiple analyses (2D and 3D). Amphotericin B was the only other antifungal that demonstrated a 2D SDR with CHF‐related events. Itraconazole demonstrated multiple SDRs with calcium channel blockers in suspect drug‐only 3D analysis. There was one other SDR with fluconazole and propanolol and three SDRs involving valproate and fluconazole that may have been do at least in part to duplicate reporting. Less specific 3D analysis including both suspect plus concomitant medications showed a greater number and variety of SDRs with multiple antifungals. Statistical reporting dependencies with CHF‐related events did not appear to be a consistent pharmacological (e.g., azole/triazole)/therapeutic (i.e., antifungal) class effect. Itraconzole was unique in the pattern of statistical reporting dependencies with CHF‐related events which is consistent with findings from independent data sets.